Bohemian Los Angeles and the making of modern politics - Hurewitz, Daniel (University of California Press, 2007)
Historian Hurewitz brings to life a vibrant and all-but-forgotten milieu of artists, leftists, and gay men and women whose story played out over the first half of the twentieth century and continues to shape the entire American landscape. In a hidden corner of Los Angeles, the personal first became the political, the nation's first enduring gay rights movement emerged, and the broad spectrum of what we now think of as identity politics was born. Portraying life over more than forty years in the hilly enclave of Edendale (now part of Silver Lake), Hurewitz considers the work of painters and printmakers, looks inside the Communist Party's intimate cultural scene, and examines the social world of gay men. He discovers why and how these communities, inspiring both one another and the city as a whole, transformed American notions of political identity with their ideas about self-expression, political engagement, and race relations.--From publisher description.